ANALISIS PELAKSANAAN PERSONAL SELLING PADA UD AMSAR MOTOR KABUN KAB. ROKAN HULU - SRI BULAN; Lie Othman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Implementation of Personal selling at UD Amsar Kabun motors are the efforts made by the salesperson or salesman in marketing the products of Honda motorcycles. In the market motorcycle products, using the theory of Philip Kotler salesman who said the implementation of the promotion Personal selling consists of: find prospects activities, communication with customers, serving customers, gather information and negotiate with consumers. Overall indicator relevanced Personal selling activities performed UD Amsar Motor Kabun, so the prospects are looking indicator is divided into 2 parts: a deal and a hot prospect prospect. To see the relationship between the implementation of the promotion Personal selling by sales volume and realization of the targets set based on a percentage of sales as well as corporate statutes. The purpose of this study is to investigate the implementation of personal selling in the motor Amsar UD Kabun Kab. Rokan Hulu.The experiment was conducted at UD Amsar Motor on Jl Raya Kabun Bangkinang-Edge Stone set sample as many as 48 research respondents consisting of customer samples UD Amsar Kabun motors, while the employee sample as many as 22 people in the census. Data collection techniques using accidental sampling method is a technique of sampling by coincidence/meet directly with researchers and coincidentally matched sample as a data source. Data obtained UD Amsar Motor Kabun obtained through questionnaires and interviews. Analysis of data obtained using qualitative descriptive methods after which the data is obtained, then analyzed, processed, and tabulated in tables and in the discussion that followed by the descriptions in order to further clarify. The data is the formal data on the number of employees and the number of customers acquired targets and actual sales of the company.2Personal selling the implementation of research results conducted byquestionnaire for the Honda brand motorcycle products are in both categories,namely 73.11% for the 48 respondents. It is explained that the implementation of thePersonal selling is looking for prospects in terms of activities, communication withcustomers, serving customers, gather information and negotiate with consumers hasbeen carried out either by a salesperson or salesman UD Amsar Motor Kabun.Keywords: Personal Selling (product, price, promotion, distribution)